Biomechanical analysis of internal fixation system stability for tibial plateau fractures - Wei, Guoqiang; Niu, Xiaofen; Li, Yuan; Chang, Tingjie; Zhang, Jianfang; Wang, Haiyan; Li, Xiaohe; He, Yujie; Wang, Ruijiang; Tian, Fei; Xu, Yangyang (Frontiers in Bioengineering and Biotechnology, 2023)
Bilateral plate fixation is utilized to treat Schatzker type V/VI tibial plateau fractures, which gives improved stability and allows the patient to bear weight early after surgery. However, secondary fractures and broken screws continue to occur postoperatively, owing mostly to incorrect weight bearing and internal fixation patterns. Previous research has overemphasized the impact of internal fixation design, plate location, and screw orientation on fracture fixation stability while ignoring the stability and fatigue properties of the internal fixation system during postoperative rehabilitation activities. The goal of this study was to look at the mechanical properties of tibial plateau fractures following internal fixation and give suggestions for postoperative weight-bearing rehabilitation. By creating a postoperative tibia model with axial loads of 500 N, 1000 N, and 1500 N and simulating standing, walking, and running conditions. The model stiffness, displacement of fractured bone fragments, titanium alloy plate, screw stress distribution, and fatigue properties of the tibia and the internal fixation system was tested. The stiffness of the model increased significantly after internal fixation. The anteromedial titanium alloy plate was the most stressed, followed by the posteromedial titanium alloy plate. Screws Nos. S7, S8, S9, S14, and S15 were under greater stress and were at safe stress levels. The relative displacement of the two medial condyles fractured bone fragments varied from 0.04-0.06 mm. Fatigue damage does not occur in the internal fixation system. Fatigue injuries develop in the tibia when subjected to cyclic loading, especially when running. The results of this study indicate that the internal fixation system tolerates some of the body's typical actions and may sustain all or part of the weight during the postoperative period early on, but avoid strenuous exercise.